Respiratory polygraphy in children with sleep‐disordered breathing. (1st April 2019) - Gudnadottir, Gunnhildur; Hafsten, Louise; Redfors, Staffan; Ellegård, Eva; Hellgren, Johan
Abstract: At‐home respiratory polygraphy has been shown to be a reliable substitute for in‐laboratory polysomnography in adults for diagnosing obstructive sleep apnea, but this is less well studied in children. One aim of this study was to examine the quality of at‐home respiratory polygraphy in children with sleep‐disordered breathing and to evaluate the interrater reliability of the results. Another aim was to study whether calibrated respiratory inductance plethysmography (RIP) flow can be used for the scoring of respiratory events when the airflow measurements are unreliable. Children aged 4–10 years, with sleep‐disordered breathing, underwent at‐home respiratory polygraphy. Of 113 polygraphies, only 46% were of acceptable quality, with missing nasal airflow being the most common problem (40%). The median recorded time with artifact‐free signal present in three traces simultaneously was 228 min (0–610 min). Seventeen polygraphy studies were selected for further study. Each study was scored by two independent scorers, with and without the nasal airflow signal present, the latter relying on RIP flow for the scoring of respiratory events. The apnea–hypopnea index (AHI) from the four different measurements was compared using intraclass correlation coefficients (ICC). Comparison of the two scorers showed moderate agreement, with (ICC = 0.66) and without (ICC = 0.53) nasal airflow. One scorer had good agreement between AHI with and without nasal airflow (ICC = 0.81), whereas the other had poor agreement (ICC = 0.12). In conclusion, the scoring of respiratory events based on RIP flow is scorer dependent even for experienced scorers. The nasal airflow signal is frequently missing in paediatric respiratory polygraphies, which limits the usefulness of the method.